Inertial Iterative Schemes for D-Accretive Mappings in Banach Spaces and Curvature Systems - Li Wei; Wenwen Yue; Yingzi Shang; Ravi P. Agarwal (Journal of Mathematics)
We propose and analyze a new iterative scheme with inertial items to approximate a common zero point of two countable d-accretive mappings in the framework of a real uniformly smooth and uniformly convex Banach space. We prove some strong convergence theorems by employing some new techniques compared to the previous corresponding studies. We give some numerical examples to illustrate the effectiveness of the main iterative scheme and present an example of curvature systems to emphasize the importance of the study of d-accretive mappings.